2010
DOI: 10.1089/acm.2009.0497
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacological and Phytochemical Evaluation of Medicinal Plants Used by the Harbang Clan of the Tripura Tribal Community of Mirsharai Area, Chittagong District, Bangladesh

Abstract: Information on phytochemicals and pharmacologic activity studies conducted on a number of the plants (used by Tripura tribal healers) by modern scientific methods validated the traditional use of a number of plants and suggested that they can form a good source of newer drugs. The survey further highlighted the importance of gathering such ethnomedicinal information for effective conservation of tribal medicinal knowledge and medicinally important plant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 125 publications
0
27
0
4
Order By: Relevance
“…Natural plant polyphenolic substances have been reported to inhibit cancer (Cognault et al, 2000). One of the most important polyphenolic classes is that of the flavonoids (Rahmatullah et al, 2010), which have been found in O. tenuiflorum (Samresh et al, 2003). According to Umadevi (2001), orientin and vicenin, which are radioprotective flavonoids found in O. tenuiflorum, exhibit activity against hydroxyl radicals.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…Natural plant polyphenolic substances have been reported to inhibit cancer (Cognault et al, 2000). One of the most important polyphenolic classes is that of the flavonoids (Rahmatullah et al, 2010), which have been found in O. tenuiflorum (Samresh et al, 2003). According to Umadevi (2001), orientin and vicenin, which are radioprotective flavonoids found in O. tenuiflorum, exhibit activity against hydroxyl radicals.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…Toward that objective, we had been conducting ethnomedicinal surveys among various large and small tribes of Bangladesh over the last few years. [4][5][6][7][8][9][10][11] The Bawm tribe is a small tribe who inhabits particularly the Rowangchhari Upazila (subdistrict) in Bandarban district. According to a population census conducted in 2002, the various ethnic groups residing in this Upazila are the Marmas (62.3% of the total population of 22,629), followed by the Tripuras (6%), Tongchongyas (5%), Murongs (4%), Bawms (4%), Chakmas (4%), Khyangs (3%), Pangkhuas (1%), and Khumis (1%).…”
Section: Introductionmentioning
confidence: 99%
“…If snake venom has entered the body, roots will taste sweet. [3][4][5][6][7][8] In the authors' surveys, emphasis has been laid on two aspects: smaller tribes, whose very existence is threatened to being engulfed within the mainstream culture, and uncommon modes of treatment among the tribal practitioners. Since the Kole and the Rai tribes have only a few members left within their respective tribal communities, and their traditional medicinal knowledge is on the is cut and the emerging juice is put in the mouth of the mother.…”
Section: Introductionmentioning
confidence: 99%